2019
DOI: 10.1097/01.hs9.0000563120.66927.63
|View full text |Cite
|
Sign up to set email alerts
|

Ps1209 nkg2d and Bcma‐car Nk Cells Efficiently Eliminate Multiple Myeloma Cells. A Comprehensive Comparison Between Two Clinically Relevant Cars

Abstract: Background:Chimeric antigen receptors (CARs) have been used in the past several years in cancer therapy to redirect immune effector cells. Despite impressive preliminary efficacy of CAR‐T cells in multiple myeloma (MM), NK cell engineering has emerged as a competitive and safer approach. NK‐92 is a universal, cheap and fast “off‐the‐shelf” cellular therapeutic previously used in clinical trials. Although modest responses with these cells have been reported in MM, their oncolytic potential can be enhanced by ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Preliminary results from a first-in-human trial of anti-CD19 CAR natural killer cells for B cell cancers showed promising efficacy, with eight (73%) of the first 13 patients responding and no evidence of cytokine release syndrome, neurotoxicity, or graft versus host disease 173. Preclinical data for CAR natural killer cells in multiple myeloma targeting CS1, BCMA, CD138, and NKG2D ligands are promising and clinical data are awaited 174175176. A table comparing CAR T cells to CAR natural killer cells has been published elsewhere 81…”
Section: Future Directionsmentioning
confidence: 99%
“…Preliminary results from a first-in-human trial of anti-CD19 CAR natural killer cells for B cell cancers showed promising efficacy, with eight (73%) of the first 13 patients responding and no evidence of cytokine release syndrome, neurotoxicity, or graft versus host disease 173. Preclinical data for CAR natural killer cells in multiple myeloma targeting CS1, BCMA, CD138, and NKG2D ligands are promising and clinical data are awaited 174175176. A table comparing CAR T cells to CAR natural killer cells has been published elsewhere 81…”
Section: Future Directionsmentioning
confidence: 99%
“…Although NK cells express the NKG2D receptor, expression of an NKG2D CAR enhances NK cell activity and should not be subject to downregulation encountered with endogenous NKG2D in AML [ 157 ]. NKG2D CAR NK-92 and primary CAR-NK cells have been evaluated pre-clinically against multiple myeloma, and activated CAR-NK cells appeared to outperform CAR-T cells in one animal model [ 147 , 158 ]. A phase I clinical trial of a haploidentical donor derived CAR-NK product targeting NKG2DL in MDS and AML has recently opened (NCT04623944).…”
Section: Car-nk: a Compelling Platform For Aml Immunotherapy?mentioning
confidence: 99%
“…NK-92 and primary CAR-NK cells equipped with NKG2D CAR have been evaluated pre-clinically. Moreover, activated NKG2D-CAR-NK cells appeared to outperform CAR-T cells in one animal model [ 157 , 158 ]. This leads to the recently opened phase I clinical trial of a haploidentical donor derived CAR-NK product targeting NKG2DL in MDS and AML (NCT04623944).…”
Section: Adoptive Cell Transfermentioning
confidence: 99%